Altmetrics for Digital Libraries : Concepts, Applications, Evaluation and Recommendations - Nuredini, Kaltrina (2021)
The volume of scientific literature is increasing and researchers have difficulties in estimating their quality and relevance. Library portals, therefore, are getting more relevant by using quality indicators to help researchers during their research process. With the growing presence of social media, altmetrics have been proposed as complementary indicators to traditional measures. Altmetrics can help to identify online attention and can appear much faster than citations. This study explores altmetrics for filtering relevant articles (in library portals) within the discipline of Economic and Business Studies literature. Firstly, it highlights the altmetrics presence from Mendeley and Altmetric.com for the journals in the above-mentioned disciplines. It presents correlations between citation and altmetrics on article and journal level, suggesting Mendeley counts as an alternative indicator to citations. Afterward, it investigates the use of altmetrics data for potential users with interests in new trends, social media platforms, and journal rankings. Lastly, it explores the behavior of economic researchers using a survey by discovering the usefulness of different altmetrics. With the findings of this study, several forms of altmetrics in library portals are discussed, using EconBiz as the proof-of-concept, to assist both researchers and libraries to identify relevant journals or articles and to cope with the information overload.